Sinensiols H–J, three new lignan derivatives from Selaginella sinensis (Desv.) Spring - Zhu, Qinfeng; Gao, Beibei; Chen, Qian; Luo, Tiantian; Xu, Guobo; Liao, Shanggao (Beilstein Journal of Organic Chemistry, 2022)
One new lignan sinensiol H (1) and two new bisnorlignans, sinensiols I and J (2 and 3), along with three known compounds were isolated from the whole plants of Selaginella sinensis. Their structures were elucidated on the basis of 1D and 2D NMR spectroscopy as well as high-resolution mass spectrometry. The absolute configuration of 1 was established by ECD calculation. Compounds 2 and 3 represent rare examples of naturally occurring 9,9'-bisnorlignans. All the isolated compounds were assayed for their inhibitory effects on LPS-induced nitric oxide production in RAW 264.7 macrophages.
Keywords: lignan derivatives; nitric oxide production inhibition; norlignans; Selaginella sinensis